Electron scattering in a helium Debye plasma - Zammit, M.; Fursa, Dmitry; Bray, Igor (Elsevier B.V, 2011)
The immense progress in the field of electron–atom scattering, where pure Coulomb potentials are involved, has been translated to collision processes in Debye plasmas. The Debye–Hückel potential is used to describe plasma Coulomb screening effects depending on the temperature and density of the plasma. We provide benchmark results of electron–helium scattering for momentum transfer cross sections, discrete excitation and ionization over a broad range of incident energies and Debye radii.